Diagnostic assessment of reading and listening in a second or foreign language: Elaborating on diagnostic principles. (July 2015) - Harding, Luke; Alderson, J. Charles; Brunfaut, Tineke
Alderson, Brunfaut and Harding (2014) recently investigated how diagnosis is practised across a range of professions in order to develop a tentative framework for a theory of diagnosis in second or foreign language (SFL) assessment. In articulating this framework, a set of five broad principles were proposed, encompassing the entire enterprise of diagnostic assessment. However, there remain questions about how best to implement these principles in practice, particularly in identifying learners' strengths and weaknesses in the less well-documented areas of SFL reading and listening. In this paper, we elaborate on the set of principles by first outlining the stages of a diagnostic process built on these principles, and then discussing the implications of this process for the diagnostic assessment of reading and listening. In doing so, we will not only elaborate on the theory of diagnosis with respect to its application in the assessment of these skills, but also discuss the ways in which each construct might be defined and operationalized for diagnostic purposes.